Expert clinical consensus in the delivery of hydrodilatation for the management of patients with a primary frozen shoulder: a modified Delphi study. (5th September 2022) - Thompson, Helen; Brealey, Stephen; Cook, Elizabeth; Hadi, Saif; Khan, Shah H. M.; Rangan, Amar
Abstract : Aims: To achieve expert clinical consensus in the delivery of hydrodilatation for the treatment of primary frozen shoulder to inform clinical practice and the design of an intervention for evaluation. Methods: We conducted a two-stage, electronic questionnaire-based, modified Delphi survey of shoulder experts in the UK NHS. Round one required positive, negative, or neutral ratings about hydrodilatation. In round two, each participant was reminded of their round one responses and the modal (or 'group') response from all participants. This allowed participants to modify their responses in round two. We proposed respectively mandating or encouraging elements of hydrodilatation with 100% and 90% positive consensus, and respectively disallowing or discouraging with 90% and 80% negative consensus. Other elements would be optional. Results: Between 4 August 2020 and 4 August 2021, shoulder experts from 47 hospitals in the UK completed the study. There were 106 participants (consultant upper limb orthopaedic surgeons, n = 50; consultant radiologists, n = 52; consultant physiotherapist, n = 1; extended scope physiotherapists, n = 3) who completed round one, of whom 97 (92%) completed round two. No elements of hydrodilatation were "mandated" (100% positive rating). Elements that were "encouraged" (≥ 80% positive rating) were the use of image guidance, local anaesthetic, normal saline, and steroids to deliver the injection. Injecting according to patient tolerance, physiotherapy, and home exercises were also "encouraged". No elements were "discouraged" (≥ 80% negative rating) although using hypertonic saline was rated as being "disallowed" (≥ 90% negative rating). Conclusion: In the absence of rigorous evidence, our Delphi study allowed us to achieve expert consensus about positive, negative, and neutral ratings of hydrodilatation in the management of frozen shoulder in a hospital setting. This should inform clinical practice and the design of an intervention for evaluation. Cite this article: Bone Jt Open 2022;3(9):701–709.